Visible-light-driven photocatalytic inactivation of Escherichia coli by magnetic Fe2O3–AgBr. (1st March 2016) - Ng, Tsz Wai; Zhang, Lisha; Liu, Jianshe; Huang, Guocheng; Wang, Wei; Wong, Po Keung
Abstract: Bacterial inactivation by magnetic photocatalyst receives increasing interests for the ease recovery and reuse of photocatalysts. This study investigated bacterial inactivation by a magnetic photocatalysts, Fe2 O3 –AgBr, under the irradiation of a commercially available light emitting diode lamp. The effects of different factors on the inactivation of Escherichia coli were also evaluated, in term of the efficiency in inactivation. The results showed that Fe2 O3 –AgBr was able to inactivate both Gram negative ( E. coli ) and Gram positive ( Staphylococcus aureus ) bacteria. Bacterial inactivation by Fe2 O3 –AgBr was more favorable under high temperature and alkaline pH. Presence of Ca 2+ promoted the bacterial inactivation while the presence of SO 4 2 − was inhibitory. The mechanisms of photocatalytic bacterial inactivation were systemically studied and the effects of the presence of various specific reactive species scavengers and argon suggest that Fe2 O3 –AgBr inactivate bacterial cells by the oxidation of H2 O2 generated from the photo-generated electron and direct oxidation of photo-generated hole. The detection of different reactive species further supported the proposed mechanisms. The results provide information for the evaluation of bacterial inactivation performance of Fe2 O3 –AgBr under different conditions. More importantly, bacterial inactivation for five consecutive cycles demonstrated Fe2 O3 –AgBr exhibited highly stable bactericidal activity and suggest that the magnetic Fe2 O3 –AgBr has great potential for water disinfection. Graphical abstract: Highlights: The bactericidal ability of magnetic Fe2 O3 –AgBr under LED lamp was demonstrated. The effects of various factors on bacterial inactivation by Fe2 O3 –AgBr were studied. Fe2 O3 –AgBr stably inactivated 7-log of Escherichia coli in five repeated cycles. Fe2 O3 –AgBr inactivated bacteria by oxidation of H2 O2 and direct oxidation of h + .